Incorporation of Soybean Husk With Different Thickening Agents in Soybean Jams - Mawar Qadijah Ishak; Siti Nasiroh Ismail; Nurul Balqish Abdul Wahab (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2024)
A series of soybean jams were prepared from soybean (Glycine max L.) with different types of thickening agent such as pectin, xanthan gum and gelatine. The jams also have been added with soybean husk as fiber enrichment, besides it helps recycling soybean by products. Soy milk was weighed and TSS (°Brix) was measured using a hand refractometer. Jams were prepared according to experimental plan. The pH of the pulp was adjusted to pH = 3.4 by addition of 1% (w/v) citric acid. The mixture was heated on a gas burner at low flame temperature. The thicken mixture was poured into 250 mL glass container and cooled under ambient condition. The elaborated jams were evaluated for physicochemical, and proximate analysis. The physicochemical and chemical characteristics evaluated were total soluble solid, TSS (°Brix), pH, energy, protein, fat, saturate fats, carbohydrate, dietary fiber, sodium, moisture, potassium, calcium and iron. Results revealed that soybean jam with xanthan gum had lower in energy (284 kcal), acceptable moisture content (31.5 g) and protein (7 g), dietary fiber (4.5 g) and potassium content (330 mg); while soybean jam with gelatine had higher protein (8.6g) and calcium (78mg) compared to the other soybean jams product. These indicated that soybean jam with functional ingredients can increase nutritional value of conventional jams.